Analysis of CSR Disclosure Practice in Sustainability Reports: A Case Study of Mining and Agriculture Companies in the Indonesia Sharia Stock Index - Nurafifah Wulandari; Rahmat Saleh (Universitas Bina Sarana Informatika, 2024)
The urgent need for CSR disclosure is not only for the company's internal needs in accountability, transparency, risk management, and business sustainability but also includes compliance with regulations and ensuring the reputation of the company's image for the trust of stakeholders, especially the surrounding community. The current situation related to the activities of mining and agricultural companies, which are risky and sensitive to the social environment and political economy, has become a major concern for various parties in Indonesia. Corporate Social Responsibility (CSR) has now become an obligation for companies that run their business activities directly or related to natural resources, which can be reported in the sustainability report. The study aims to determine the description of CSR disclosure practices in sustainability reports with the Sharia Enterprise Theory (SET) approach. The measurement indicators used are the GRI Standard and Sharia compliance, which consists of 4 categories in measuring CSR disclosure carried out by the content analysis method. This research was conducted on companies listed on the Indonesian Sharia Stock Index (ISSI). The number of samples in this study was 11 companies consisting of 6 mining companies and five agricultural companies obtained by purposive sampling technique. This study did not include the 2020-2024 period in the analysis because the global economic crisis due to the COVID-19 pandemic made companies change their priorities. The results showed that, in general, the concept of SET in CSR disclosure has been applied by companies in terms of habluminallah and habluminannas, with an average disclosure of 47 items out of 123 items per company. The company that disclosed the most was PT Timah Tbk, with a score of 65 items, and the lowest was PT Austindo Tbk, which had 30 items. Our findings have alternative implications for the government in several ways, including strengthening regulations and policies, supervision and law enforcement, incentives and support, and pressure on companies to provide space for public involvement and participation.